2017
DOI: 10.1002/ptr.5974
|View full text |Cite
|
Sign up to set email alerts
|

Melaleuca alternifoliaand its application against dental plaque and periodontal diseases: A systematic review

Abstract: This is a systematic review of clinical and laboratory studies evaluating the effect of Melaleuca alternifolia on periodontopathogens, dental plaque, gingivitis, periodontitis, and inflammatory responses. The PubMed, Cochrane, Web of science, Bireme, Lilacs, Prospero, Open Grey, and Clinical Trials databases were searched to identify potentially eligible studies through October 2016. Of 1,654 potentially eligible studies, 25 were included in the systematic review. Their methodology was evaluated through the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 56 publications
(136 reference statements)
0
28
0
6
Order By: Relevance
“…Several studies found that the M. alternifolia essential oil and its main components are effective against pathogenic flora. Due to its broad spectrum, a strong inhibition against gram-positive and gram-negative bacteria, including A. actinomycetemcomitans , S. gordonii , and S. mutans , was found [92,93]. The antibacterial effect of Splat Organic may be due to its Aloe vera and papain content.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that the M. alternifolia essential oil and its main components are effective against pathogenic flora. Due to its broad spectrum, a strong inhibition against gram-positive and gram-negative bacteria, including A. actinomycetemcomitans , S. gordonii , and S. mutans , was found [92,93]. The antibacterial effect of Splat Organic may be due to its Aloe vera and papain content.…”
Section: Discussionmentioning
confidence: 99%
“…For chemical compounds such as cineol, terpinen-4-ol, terpinolene, cymene, limonene, sabinene, terpinene, pinene viridiorol, and globulol, their chemical compositions include mostly terpenic compounds [52]. Melaleuca alternifolia is used for periodontitis [54], bad breath, relief from bleeding gums and plaque [55]. The Melaleuca alternifolia essential oil is extracted from leaves and terminal branches by using the steam distillation method.…”
Section: Melaleuca Alternifolia (Maiden and Betche) Cheelmentioning
confidence: 99%
“…Result: Approximal plaque index (API)-Before treatment; 64.58 ± 22.38%. After treatment, 7 days-(49.00 ± 25.32%, p < 0.006) and after 28 days-(39.39 ± 20.60%, p < 0.0002) [53] Periodontitis [54], Relieve from bad breath, bleeding gums, and plaque [55] Acacia nilotica (Babul) India, Nepal, Pakistan, Arabian Peninsula, Africa, South Africa, Egypt [56] Hydrodistillation method and analyzed by GC-FID and GC/MS. Essential oil extracted from the bark, leaves [57] Menthol (34.9%), limonene (15.3%), α-Curcumene (6.9%) and carvacrol (4.1%) [57] In vitro (antibacterial) on Lactobacillus acidophilus, Streptococcus sanguinis, S. salivarius, and Aggregatibacter actinomycetemcomitans.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of its properties, it is becoming more famous and is getting utilized in dermatology, oncology, and dentistry. [13][14][15][16][17][18][19][20] Eur J Dent 2020; 14:55-62 Tea Tree Oil in the Treatment of Gingivitis Ripari et al…”
Section: Introductionmentioning
confidence: 99%